Strategi Pembelajaran Al-Qur’an dengan Pendekatan Tahsin dalam Memperbaiki Kualitas Bacaan Al-Qur’an Santri di Pondok Pesantren - Kusuma, Radhika Abi; Astutik , Anita Puji (Hikmah, 2024)
One of the fundamental problems faced by Muslims is the low ability to read and write the Qur'an properly and correctly among the younger generation. The determination of learning strategies becomes the most important part in this process, especially the learning strategy of the Qur'an with the Tahsin approach. This approach is very necessary because the concepts of learning strategies are not easy to implement. Therefore, the purpose of this study is to describe the Al-Qur’an  learning strategy with the Tahsin approach in improving the quality of Al-Qur’an  reading of students in Islamic Boarding Schools. This research uses a qualitative method with a descriptive approach. The research location is Bangsal Islamic Boarding School. The data collection methods used include observation, interviews, and documentation. The data analysis technique uses descriptive analysis. The results showed that the Al-Qur’an  learning strategy with the Tahsin approach at the Bangsal Islamic Boarding School was carried out through a leveling strategy consisting of three classes: reading class 1, reading class 2, and reading class 3, with tajweed and makharijul letter material tailored to different levels of difficulty. Supporting and inhibiting factors for learning implementation come from two main factors, namely internal factors and external factors. This research has implications for improving the quality of students' Qur'an reading.